Optimizing incentive plan design: A case study - Alec Levenson; Cindy Zoghi; Michael Gibbs; George Benson (Institute for the Study of Labor (IZA), 2011)
We study effects of a firm's attempt to optimize an existing incentive scheme to increase sales growth for direct store delivery workers. Before optimization workers reported Ratchet Effects that lowered productivity. The altered incentive plan offered higher compensation for increased sales relative to a sales growth target, and lower compensation for failing to meet the target. We gathered data on performance and attitudes at pilot and control sites before and after the change. Relative to control sites, sales growth increased in the pilot sites by two percent, a meaningful contribution to firm profits. We find no change in distortion of effort or manipulation of the performance measure. Workers did not substantially change number of hours worked, though allocation of time across tasks changed slightly. Despite increased productivity, workers continued to report Ratchet Effects after the change. We also find that an unplanned price increase midway through a fiscal year affected the extent of Ratchet Effects that year.
urn:nbn:de:101:1-20111011201
Keywords: M52; J33; M12; L81; 330; incentives; ratchet effect; Leistungsanreiz; Handel; Direktmarketing; Kundendienst; Arbeitsproduktivität; USA